Recent Advances in Soft Computing Proceedings of 23rd International Conference on Soft Computing (MENDEL 2017) Held in Brno, Czech Republic, June 20-22, 2017 - Matoušek, Radek (Advances in Intelligent Systems and Computing, 2019)
Soft computing is a formal area of computer science and an important aspect of artificial intelligence. Professor Lotfi A. Zadeh introduced the first definition of soft computing in the early 1990s: "Soft computing principles differs from hard (conventional) computing in that, unlike hard computing, it is tolerant of imprecision, uncertainty, partial truth, and approximation". The role model for soft computing is the human mind and its cognitive abilities. Techniques used for solving problems with this soft computing approach include but are not limited to fuzzy logic, neural computing, evolutionary computation, swarm intelligence, machine learning, etc. Image processing is a complex process, in which image processing routines and domain-dependent interpretation steps often alternate. In many cases image processing has to be extensively intelligent regarding the tolerance of imprecision and uncertainty. A typical application is computer vision in robotics. It is about taking concepts from nature and applying them to the design of real-world engineered systems. This proceeding book presents selected papers from the MENDEL conference held in Brno, Czech Republic in June 2017. It includes three chapters that present recent advances in soft computing including intelligent image processing. The MENDEL conference was established in 1995 and is named after the scientist and Augustinian priest Gregor J. Mendel, who discovered the famous Laws of Heredity. The main aim of the conference is to create an opportunity for students, academics and researchers to exchange ideas and novel research methods on a yearly basis.